The Effect of a Guided Inquiry Learning Model Assisted by a Virtual Laboratory on Students' Cognitive Learning Outcomes - Wulandari; Saidil Mursali; Septiana Dwi Utami; Sri Nopita Primawati (Lombok Institute, 2025)
This study aimed to investigate the impact of a guided inquiry learning model supplemented by a virtual laboratory on students' cognitive learning outcomes. The study was motivated by low cognitive achievement and limited laboratory facilities in schools. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design. The sample comprised two Grade X classes at SMA Negeri 2 Labuapi, selected through cluster random sampling. Research instruments included a cognitive learning outcomes test and an observation sheet related to cognitive learning outcomes. Data were analyzed using the normalized gain (N-Gain) test and ANCOVA. The results showed that the N-Gain of the experimental class (0.50) was higher than that of the control class (0.36), and the ANCOVA produced a significance value of 0.000 (< 0.05), indicating a significant effect of the learning model on improving cognitive learning outcomes. These findings suggest that guided Inquiry assisted by a virtual laboratory is more effective than conventional instruction in developing cognitive outcomes, including the ability to analyze information, construct arguments, and draw logical conclusions. This model is relevant for 21st-century science learning, especially in schools with limited laboratory facilities.